Edukasi Gizi Seimbang Menggunakan Media Leaflet Mempengaruhi Pencegahan Kurang Energi Kronik (KEK) Remaja Putri di SMP Negeri 12 Kota Makassar - Muchtar, Nur Laila; Hartono, Rudy; Fanny, Lydia; Sirajuddin, Sirajuddin (Yayasan Mandar Indonesia, 2023)
Nutrition education is a method and effort to improve nutrition knowledge and eating behavior so as to create optimal nutritional status. Nutrition education is an educational approach to improve adolescents' knowledge and attitudes towards nutrition. The higher the nutritional knowledge will affect the attitude and behavior of food consumption. This research aims to determine the effect of balanced nutrition education on increasing the knowledge of adolescent girls with chronic energy deficiency. This study uses the type of experimental research with a one group pre-post test design that involves one group. The place where this research was conducted was the SMP Negeri 12 Makassar City. There is an effect of providing nutrition education on increasing the knowledge of adolescent girls with chronic energy deficiency. The results of statistical analysis showed a p-value of 0.000. There is an effect of providing nutrition education on increasing the knowledge of adolescent girls with chronic energy deficiency.